Amelioration of human acute lymphoblastic leukemia (ALL) cells by ZnO-TiO2-Chitosan-Amygdalin nanocomposites - Elderdery, Abozer Y.; Alzahrani, Badr; Alanazi, Fehaid; Hamza, Siddiqa M.A.; Elkhalifa, Ahmed M.E.; Alhamidi, Abdulaziz H.; Alabdulsalam, Abdulrahim A.; Mohamedain, A.; Kumar, Suresh S.; Pooi, Ling Mok (Elsevier, 2022)
The present study aims to study the cytotoxicity of ZnO-TiO2-Chitosan-Amygdalin nanocomposites (ZnO-TiO2-Chitosan-Amygdalin) on T lymphoblast cancer cells (MOLT-4). In a study, nanocomposites containing 2.5 to 15 µg/ml MTT were screened for their anticancer activity. Its anticancer properties were significantly higher than those of other nanocomposites with an IC50 value of 10.34 µg/ml. We studied the mechanism of action for cytotoxic cell death by fluorescence microscopy using Acridine Orange/EtBr (AO/EtBr) and Rhodamine 123 staining procedures. Using DCFH-DA, ZnO-TiO2-Chitosan-Amygdalin nanocomposites were analyzed to determine ROS production. The change in apoptotic protein expression for the 24 h following treatment with MOLT-4 cells for Caspase-3, 8, and 9. Nanocomposites containing ZnO-TiO2-Chitosan-Amygdalin increased the number of early and late apoptotic cells in MOLT-4 cells. ZnO-TiO2-Chitosan-Amygdalin nanocomposites also enhanced mitochondrial apoptosis through Caspase cascade signaling. MOLT-4 cells phosphorylated Caspase cascade in response to ZnO-TiO2-Chitosan-Amygdalin nanocomposites. Compared to the control group, the cancer cells treated with ZnO-TiO2-Chitosan-Amygdalin nanocomposites significantly arrest the proliferation and induces cleavage of pro-apoptotic proteins which leads to apoptotic cell death. Accordingly, ZnO-TiO2-Chitosan-Amygdalin nanocomposites might be effective against T lymphoblast cancer.